Hopelessness and burnout in Italian healthcare workers during COVID-19 pandemic: the mediating role of trait emotional intelligence - Epifanio, Maria Stella; La Grutta, Sabina; Piombo, Marco Andrea; Riolo, Martina; Spicuzza, Vittoria; Franco, Marianna; Mancini, Giacomo; De Pascalis, Leonardo; Trombini, Elena; Andrei, Federica (Frontiers in Psychology, 2023)
Objective: The study aims to assess the impact of COVID-19 on healthcare workers’ (HCW) work-related stress during the first wave of the pandemic in Italy. The main objective is to investigate the existence of a positive correlation between hopelessness and burnout, assuming that burnout may be a risk factor for the development of hopelessness, and to analyse the role that TEI and changes in workload could have in this relationship. Furthermore, evaluate any significant differences in burnout and hopelessness levels in the function of some demographic variables such as gender, professional profiles, and different working zones of Italy, to better understand how the diverse diffusion of pandemic had affected Italian HCW. Methods: An online survey was between April and June, 2020, with 562 responses among nurses (52.1%) and physicians (47.9%). Demographics and changes in workload and work conditions were collected through an ad-hoc questionnaire. The Trait Emotional Intelligence Questionnaire-Short Form (TEIQue-SF;), The Beck Hopelessness Scale (BHS), and the Link Burnout Questionnaire (LBQ) were used to assess Trait Emotional Intelligence (TEI), hopelessness and burnout respectively. Results: correlation analysis showed a significant positive relationship between hopelessness and each burnout dimension. TEI showed negative correlations both with burnout dimensions and hopelessness. Significant differences in burnout and hopelessness levels emerged as a function of some demographic variables such as gender, professional profiles (nurses or physicians), and different working zone of Italy (northern or southern). Results showed that TEI partially mediated the relationship between hopelessness and every burnout dimension, while the interaction of changes in workload was non- significant. Discussion: The mediating role of TEI in the burnout-hopelessness relationship partly explains the protective role that individual factors had on HWC mental health. Our findings support the need to integrate considerations on both psychological risk and protective factors into COVID-19 care, including the monitoring of psychological symptoms and social needs especially among healthcare workers.